BStGer SK.2018.10 vom 26. Oktober 2018 - Bundesstrafgericht (2018)
Confiscation (art. 59 ch. 1 aCP; art. 70 al. 1 CP), créance compensatrice (art. 59 ch. 2 al. 1 aCP; art. 71 al. 1 CP), séquestre (art. 59 ch. 2 al. 3 aCP; art. 71 al. 3 CP) Renvoi du TF (arrêts 6B_664/2014 et 6B_667/2014)